The bottle imp of Bright House - Llewellyn, Tom (Thomas Richard), 1964- (Holiday House, 2018)
Thirteen-year-old Gabe buys a bottle bearing an imp that will grant his every wish, but someone else will pay the price and, if he dies while owning the bottle, he will lose his soul.